AUTHENTICATED ENCRYPTION WITH ASSOCIATED DATA SCHEME FOR LORA-BASED MQTT-SN PROTOCOL - Setya Pramayoga, Adhe
Internet of Things (IoT) paradigm describes interaction of data exchange between physical objects (sensors or actuators) with a control or data analytic services over the internet. Most physical objects are devices with limited computing capacity, less storage, and constrained resources. MQTT (Message Queue Telemetry Transport) protocol is defined as data exchange protocol that can be implemented on devices with these characteristics. MQTT is designed to run on TCP/IP. UDP-based communication media technologies, such as ZigBee and LoRa, can use a lightweight version of MQTT, namely MQTT-SN. Several studies show the implementation of MQTT-SN at the physical layer of LoRa. However, it needs improvement on security aspect protections of messages that containing sensitive data. In this paper, a simulation of the MQTT-SN protocol on LoRa devices is carried out by adding AEAD (Authenticated Encryption with Associated Data) scheme to protect confidentiality and message authenticity. Two algorithms, AES-GCM and ChaCha20-Poly1305 were tested on resource constrained devices to know the performance of the proposed scheme. The results show that the AEAD scheme can increase security in implementing the MQTT-SN protocol on LoRa devices by only increasing the amount of payload, memory consumption, and processing time that can still be tolerated.